Fat chance!: Obesity and the transition from unemployment to employment - Marco Caliendo; Wang-Sheng Lee (Institute for the Study of Labor (IZA), 2011)
This paper focuses on estimating the magnitude of any potential weight discrimination by examining whether obese job applicants in Germany get treated or behave differently from non-obese applicants. Based on two waves of rich survey data from the IZA Evaluation dataset, which includes measures that control for education, demographic characteristics, labor market history, psychological factors and health, we estimate differences in job search behavior and labor market outcomes between obese/overweight and healthy weight individuals. Unlike other observational studies which are generally based on obese and non-obese individuals who might already be at different points in the job ladder (e.g., household surveys), in our data, individuals are newly unemployed and all start from the same point. The only subgroup we find in our data experiencing any possible form of labor market discrimination is obese women. Despite making more job applications and engaging more in job training programs, we find some indications that they experienced worse (or at best similar) employment outcomes than healthy weight women. Obese women who found a job also had significantly lower wages than healthy weight women.
urn:nbn:de:101:1-201106224766
Keywords: I10; I12; J23; J70; 330; obesity; discrimination; employment; labor demand